Hypobaric hypoxia affects the reproductive physiology of dairy cattle - Kumari, Preeti; Bharti, Vijay K; Kumar, Krishna; Sharma, Indu (Animal Reproduction Update, 2023)
As the altitude increases, the partial pressure of oxygen decreases, leading to hypoxic conditions and ultimately disturbing body homeostasis and affecting neuroendocrine function in cattle. These physiological changes cause low conception rate, early embryonic death, low fertility, etc., in cattle and other livestock species. So far, cattle's reproductive health associated with high-altitude hypoxic conditions has rarely been studied concerning reproductive physiology, endocrinology, and physio-biochemical perspective. Hence, this review discusses various physiological changes, hormonal disturbance, placenta development, haematological and biochemical changes, etc., which are associated with and affect cattle's reproductive physiology.
Keywords: Hypobaric hypoxia; oxygen-dissociation curve; reproduction; placenta; hormone; reproductive physiology; dairy cattle